Synthesis of Novel Hydroxymethyl-Substituted Fused Heterocycles - Holmes, Jane L.; Almeida, Lynsie; Barlaam, Bernard; Croft, Rosemary A.; Dishington, Allan P.; Gingipalli, Laksmaiah; Hassall, Lorraine A.; Hawkins, Janet L.; Ioannidis, Stephanos; Johannes, Jeffrey W.; McGuire, Thomas M.; Moore, Jane E.; Patel, Anil; Pike, Kurt G.; Pontz, Timothy; Wu, Xiaoyun; Wang, Tao; Zhang, Hai-Jun; Zheng, Xiaolan (Synthesis, 2016)
Examples of hydroxymethylated analogues of heteroaryl cores such as quinazolin-4-ones, isoquinolin-1(2H)-ones, pyrido[3,4-d]pyrimidin-4(3H)-ones, chromen-4-ones and pyrrolo[2,1-f][1,2,4]triazin-4(3H)-ones are sparse or non-existent in the scientific literature. We have demonstrated that such compounds are accessible by using standard procedures from readily available raw materials.
Keywords: cross-coupling; fused-ring systems; heterocycles; quinazolinones; isoquinolinones; chromenones; triazinones